BaRTv2: a highly resolved barley reference transcriptome for accurate transcript‐specific RNA‐seq quantification. (19th July 2022) - Coulter, Max; Entizne, Juan Carlos; Guo, Wenbin; Bayer, Micha; Wonneberger, Ronja; Milne, Linda; Schreiber, Miriam; Haaning, Allison; Muehlbauer, Gary J.; McCallum, Nicola; Fuller, John; Simpson, Craig; et al.
SUMMARY: Accurate characterisation of splice junctions (SJs) as well as transcription start and end sites in reference transcriptomes allows precise quantification of transcripts from RNA‐seq data, and enables detailed investigations of transcriptional and post‐transcriptional regulation. Using novel computational methods and a combination of PacBio Iso‐seq and Illumina short‐read sequences from 20 diverse tissues and conditions, we generated a comprehensive and highly resolved barley reference transcript dataset from the European 2‐row spring barley cultivar Barke (BaRTv2.18). Stringent and thorough filtering was carried out to maintain the quality and accuracy of the SJs and transcript start and end sites. BaRTv2.18 shows increased transcript diversity and completeness compared with an earlier version, BaRTv1.0. The accuracy of transcript level quantification, SJs and transcript start and end sites have been validated extensively using parallel technologies and analysis, including high‐resolution reverse transcriptase‐polymerase chain reaction and 5'‐RACE. BaRTv2.18 contains 39 434 genes and 148 260 transcripts, representing the most comprehensive and resolved reference transcriptome in barley to date. It provides an important and high‐quality resource for advanced transcriptomic analyses, including both transcriptional and post‐transcriptional regulation, with exceptional resolution and precision. Significance Statement: We have developed BaRTv2.18, which represents the most comprehensive and resolved reference transcriptome in barley ( Hordeum vulgare ) to date. Novel methods are applied to analyze Iso‐seq data that accurately determine the transcripts from start to end (splice junctions, transcript start and end sites). It will prove to be an important and high‐quality resource for the barley research community to carry out advanced transcriptomic analyses, including both transcriptional and post‐transcriptional regulation, with exceptional resolution and precision